Evaluation of the Effectiveness of Strategies for Developing Mathematical Problem-Solving Abilities - Fitri, Musyrifah (Lembaga Riset Mutiara Akbar, 2023)
This research aims to evaluate the effectiveness of strategies for developing mathematical problem-solving abilities at certain educational levels. Mathematical problem-solving is a critical skill required in various contexts of daily life and has a significant impact on the ability to understand mathematical concepts. The research method involved two groups of students, namely the control group and the treatment group. The control group followed conventional learning, while the treatment group was given special development strategies to improve mathematical problem-solving abilities. Research instruments include problem-solving tests, observations, and questionnaires. Data analysis was carried out through statistical techniques, including descriptive analysis and hypothesis testing. The research results showed that the group of students who applied the development strategy experienced a significant increase in mathematical problem-solving abilities compared to the control group. This research contributes to the practical understanding of the effectiveness of strategies for developing mathematical problem-solving abilities in specific educational environments. The implications of this research can be used as a guide to improve learning approaches in the context of developing mathematical problem-solving abilities at the relevant educational level.